2020
DOI: 10.3390/jcm9020496
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Patterns after Surgery in Patients with Different Endometriosis Subtypes: A Long-Term Hospital-Based Cohort Study

Abstract: Recurrence of endometriosis after surgery constitutes a serious challenge. Whether there is an evolution of lesion subtypes with each recurrence and whether certain lesions subtypes tend to recur faster than others is not adequately addressed. Medical records of all patients who underwent surgery for endometriosis between 1997 and 2018 in the Department of Gynecology and Obstetrics, University of Bern, were reviewed. Inclusion criteria was surgically confirmed endometriosis recurrence, defined as a subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 36 publications
3
24
0
2
Order By: Relevance
“…Again, this does not exclude other hypotheses in the pathogenesis of endometriosis. Remarkably, recently, it was found that the time to recurrence is independent of the three endometriotic subtypes (ovarian, peritoneal, and DIE) at first surgery [ 34 ].…”
Section: Endometriosismentioning
confidence: 99%
“…Again, this does not exclude other hypotheses in the pathogenesis of endometriosis. Remarkably, recently, it was found that the time to recurrence is independent of the three endometriotic subtypes (ovarian, peritoneal, and DIE) at first surgery [ 34 ].…”
Section: Endometriosismentioning
confidence: 99%
“…A recurrence that led to repeated surgery developed in 21.8% of patients in our sturdy population. This value falls into the lower range of data published in the literature, where a recurrence rate of between 18.9 and 57% after 5 years is specified [ 18 – 20 , 22 , 38 40 ]. It should be kept in mind that in some of our patients, 14 years had passed since surgery.…”
Section: Discussionmentioning
confidence: 82%
“…Unfortunately, the rate of recurrence after endometriosis surgery is considerable at times and varies between 6 and 67% after 5 years [ 18 – 22 ]. The rate of recurrence increases in relation to the extent of endometriosis at baseline [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nirgianakis et al evaluated the recurrence patterns after surgery depending on the different endometriosis subtypes: superficial peritoneal endometriosis, ovarian endometrioma and deep infiltrating endometriosis. Although peritoneal endometriosis and ovarian endometrioma are more likely to present with the same subtype at recurrence, the time to recurrence was independent of the lesion subtype at first surgery [22].…”
Section: Stage-related Surgical Procedures and Postoperative Rate Of mentioning
confidence: 89%
“…Unfortunately, the rate of recurrence after endometriosis surgery is considerable at times and varies between 6% and 67% after five years [18][19][20][21][22]. The rate of recurrence increased the more extensive the baseline finding [18].…”
Section: Postoperative Recurrencementioning
confidence: 99%